Stylistic Devices as a Means of Enhancing Thematic Cohesion in Literary Texts - Rahmatova Sitora Samadovna; Arustamyan Yana Yurevna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the role of stylistic devices in strengthening the conceptual and thematic cohesion of literary texts. It examines how literary techniques such as metaphor, symbolism, imagery, and repetition contribute to a unified narrative and enhance the reader’s comprehension and emotional engagement. By analyzing selected examples from both classical and contemporary literature, the study demonstrates that the deliberate use of stylistic devices not only enriches textual aesthetics but also reinforces the underlying thematic framework, allowing authors to communicate complex ideas more effectively.